PENGARUH KEPRIBADIAN TERHADAP KINERJA MELALUI SELF EFFICACY DAN KEPUASAN KERJA PADA DINAS SOSIAL PROVINSI JAWA TENGAH - Sugondo, 12.42.02.0035; Rijangti, Tristiana (Jurnal Mahasiswa Pasca Sarjana, 2014)
The success of an organization is strongly influenced by the performance of, any organization is always seeking to improve performance to achieve the vision and mission of the organization so that goals can be achieved optimally. Good personality will improve the performance of employees in the organization. This study aims to analyze the influence of personality on performance through self-efficacy and job satisfaction in the Social Service of Central Java Province. The sample of this study were employees of Social Service of Central Java Province who had worked ≥ 5 years as many as 171 people / respondent. Based on the results of the analysis showed that personality variables, self-efficacy and job satisfaction partially or simultaneously positive effect on employee performance Dinsos Central Java province in carrying out their duties and responsibilities. Based on the analysis of self-efficacy variable paths and job satisfaction is not a mediating effect of personality variables on performance due to a stronger influence of personality variables. Keywords: Personality, Self-Efficacy, Job Satisfaction, and Performance